Domain adversarial training for speech enhancement - Hou, Nana (2020)
The performance of deep learning approaches to speech enhancement degrades significantly in face of mismatch between training and testing. In this paper, we propose a domain adversarial training technique for unsupervised domain transfer, that 1) overcomes domain mismatch, and 2) provides a solution to the scenario where we only have noisy speech data, and we don’t have clean-noisy parallel data in the new domain. Specifically, our method includes two parts that are jointly trained, 1) an enhancement net to map noisy speech to clean speech by indirectly estimating a mask with a spectrum approximation loss, and 2) a domain predictor to distinguish between domains. As the proposed approach is able to adapt to a new domain only with noisy speech data in target domain, we call it an unsupervised learning technique. Experiments suggest that our approach delivers voice quality comparable with other supervised learning techniques that require clean-noisy parallel data.